Pengaruh Minat dan Kemandirian Belajar terhadap Keterampilan Menulis Teks Eksposisi - Lulu' Ur Rohmah; Sumaryoto Sumaryoto; Mamik Suendarti (Universitas Indraprasta PGRI, 2023)
The purpose of this research is to find: (1) the effect of interest and independence in learning on the skills of writing exposition text, (2) the effect of interest in learning on the skill of writing exposition text, and (3) the effect of independent learning on the skill of writing exposition text. The research method used in this research is a survey and the model used is multiple linear regression. The result of the study concluded (1) There is a significant effect of interest and independence in learning together on the skills of writing exposition texts for State Senior High School students in Depok City. This is evidenced by the acquisition of the value of Sig. = 0.000 > 0.05 and = 39.380. (2) There is a significant effect of interest in learning on the skills of writing exposition texts for State Senior High School students in Depok City. This is evidenced by the acquisition of the value of Sig. = 0.000 < 0.05 and = 3.705. (3) There is a significant effect of learning independence on the skills of writing exposition texts for State Senior High School students in Depok City. This is evidenced by the acquisition of the value of Sig. = 0.000 < 0.05 and = 4.628. Accordingly, it can be concluded that the high interest and independence in learning have an effect on improving the skills of writing expository texts.Keywords: Interest in Learning, Independence in Learning, Writing Exposition Text Skills.